PERAN PEMERINTAH TERHADAP PRAKTIK PELAYANAN TELEMEDICINE ANTARA DOKTER DAN PASIEN DI INDONESIA DARI PERSPEKTIF YURIDIS - Farhannuddin (2020)
This research aims at analyzing government's role in doctor-patient telemedical practice in Indonesia from juridical perspective. Discussion in this paper is directed to library research, statute approach and other relevant documents approach. Telemedical service implementation in Indonesia still causes legal polemics related to the dimension of doctor practice permit as telemedical service provider, regulation of telemedical service provider's rights and obligations, human resources standardization of telemedical service provider and accountability of medical record security guarantee. Government's role in supervising doctor-patient telemedical practice in Indonesia with categorization of current telemedical service must be conducted at authorized health service facility. The government also needs to stipulate a detailed regulation on doctor-patient telemedical service in collaboration with various sectors of every field.